Traduire « sous verre » ou « à la vitre » : l’imaginaire de la transparence en traduction - Solange Arber (Itinéraires)
Images of transparency and specifically glass metaphors are often used in modern discourses about translation. However, the notion of transparency is deeply ambiguous since it means at the same time vision and obliteration, presence and absence, appearance and disappearance. From Chateaubriand who claimed to have “traced Milton’s poem through a glass,” to the German translator Elmar Tophoven who envisioned an “under glass” type of translation, to Walter Benjamin, Georges Mounin, Lawrence Venuti and Antoine Berman, the overview of the uses of transparency in translation discourses reveals the contradictions within this imagery and raises questions about transparency as a paradigm in translation studies.